2014
DOI: 10.3389/fpsyt.2014.00069
|View full text |Cite
|
Sign up to set email alerts
|

Drug Use among Iranian Drivers Involved in Fatal Car Accidents

Abstract: Background: Although the problem of substance use among drivers is not limited to certain parts of the world, most epidemiological reports on this topic have been published from industrial world.Aim: To investigate pattern of drug use among Iranian drivers who were involved in fatal road accidents.Methods: This study enrolled 51 Iranian adults who were involved in fatal vehicle accidents and were imprisoned thereafter. Data came from a national survey of drug abuse that was done among Iranian prisoners. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 43 publications
2
16
1
Order By: Relevance
“…In addition, 90.6% abused two or more substances concomitantly and 9.4% had single substance. These results are comparable to those reported by Assari et al (2014) who reported that, 60% of Iranian drivers who are involved in fatal car accidents use drugs. However, they found opioids to be the most common abused substance followed by cannabis.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, 90.6% abused two or more substances concomitantly and 9.4% had single substance. These results are comparable to those reported by Assari et al (2014) who reported that, 60% of Iranian drivers who are involved in fatal car accidents use drugs. However, they found opioids to be the most common abused substance followed by cannabis.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, frequency of smoking was greater than drug use in Zahedan drivers, which was relatively low, compared to previous studies in Iran (5, 16) and worldwide (11-13). A study conducted in Iran (18) reported the prevalence of smoking in drivers 25%.…”
Section: Discussioncontrasting
confidence: 79%
“…Besides, the above studies were conducted several years ago, when use of compounds that make opiates undetectable in blood was not so common among drivers. Furthermore, high frequency of drug use among the smoking drivers and high frequency of smoking drivers (5, 11, 12, 16) also show why drug use was reported so low in this study.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations